A Novel Controlled PTEN-Knockout Mouse Model for Prostate Cancer Study - Liu, Sen; Zhang, Bing; Rowan, Brian G.; Jazwinski, S. Michal; Abdel-Mageed, Asim B.; Steele, Chad; Wang, Alun R.; Sartor, Oliver; Niu, Tianhua; Zhang, Qiuyang (Frontiers in Molecular Biosciences, 2021)
Prostate cancer (PCa) is associated with advanced age, but how age contributes to prostate carcinogenesis remains unknown. The prostate-specific Pten conditional knockout mouse model closely imitates human PCa initiation and progression. To better understand how age impacts PCa in an experimental model, we have generated a spatially and temporally controlled Pten-null PCa murine model at different ages (aged vs. non-aged) of adult mice. Here, we present a protocol to inject the Cre-expressing adenovirus with luciferin tag, intraductally, into the prostate anterior lobes of Pten-floxed mice; Pten-loss will be triggered post-Cre expression at different ages. In vivo imaging of luciferin signal following viral infection confirmed successful delivery of the virus and Cre activity. Immunohistochemical staining confirmed prostate epithelial-specific expression of Cre recombinase and the loss of Pten and activation of P-Akt, P-S6, and P-4E-BP1. The Cre-expression, Pten ablation, and activated PI3K/AKT/mTOR pathways were limited to the prostate epithelium. All mice developed prostate epithelium hyperplasia within 4 weeks after Pten ablation and prostatic intraepithelial neoplasia (PIN) within 8 weeks post-Pten ablation. Some PINs had progressed to invasive adenocarcinoma at 8 to 16 weeks post-Pten ablation. Aged mice exhibited significantly accelerated PI3K/AKT/mTOR signaling and increased PCa on-set and progression compared to young mice. The viral infection success rate is ~80%. This model will be beneficial for investigations of cancer-related to aging.